Impact of Hemodynamic Instability and Organ Malperfusion in Elderly Surgical Patients Treated for Acute Type A Aortic Dissection. Issue 11 (10th September 2015) - Zindovic, Igor; Sjögren, Johan; Bjursten, Henrik; Danielsson, Eric; Ingemansson, Richard; Nozohoor, Shahab
Abstract Objective Recent studies indicate acceptable survival rates in elderly patients treated surgically for acute type A aortic dissection (aTAAD). However, the impact of preoperative hemodynamic compromise or organ malperfusion on outcomes of such patients is still unclear. Methods In a retrospective study of 341 patients, 101 qualified as elderly (≥70 years old). Subjects were further grouped by clinical presentation, using the Penn classification. Univariate and multivariable analyses were conducted to identify variables reflecting in‐hospital and long‐term mortality. Results Relative to younger subjects, elderly patients showed significantly higher rates of in‐hospital mortality (24.8% vs. 14.6%, p = 0.025) and DeBakey type 2 dissections at presentation (40% vs. 18% p < 0.001), with significantly fewer presenting as Penn class Ab (p = 0.010). Penn class Ac was identified as an independent predictor of in‐hospital mortality at all ages. Estimated long‐term survival was poorer in the elderly (log rank p < 0.001); but in‐hospital mortality, based on Penn classification, was similar for both age groups. Survival rates of Penn class Aa subjects at one, five, and 10 years were lower in elderly (vs. younger) patients (79 ± 5.6% vs. 90 ± 2.7%, 68 ± 6.7% vs. 80 ± 3.9%, and 39 ± 10.3% vs. 75 ± 4.6%, respectively; log rank p < 0.001). Conclusion Overall in‐hospital mortality is higher in elderly patients surgically treated for aTAAD. Malperfusion and/or hemodynamic instability at presentation confer a dismal prognosis, independent of patient age.